Short- and long-term effects of diving on pulmonary function. (29th March 2017) - Tetzlaff, Kay; Thomas, Paul S.
The diving environment provides a challenge to the lung, including exposure to high ambient pressure, altered gas characteristics and cardiovascular effects on the pulmonary circulation. Several factors associated with diving affect pulmonary function acutely and can potentially cause prolonged effects that may accumulate gradually with repeated diving exposure. Evidence from experimental deep dives and longitudinal studies suggests long-term adverse effects of diving on the lungs in commercial deep divers, such as the development of small airways disease and accelerated loss of lung function. In addition, there is an accumulating body of evidence that diving with self-contained underwater breathing apparatus (scuba) may not be associated with deleterious effects on pulmonary function. Although changes in pulmonary function after single scuba dives have been found to be associated with immersion, ambient cold temperatures and decompression stress, changes in lung function were small and suggest a low likelihood of clinical significance. Recent evidence points to no accelerated loss of lung function in military or recreational scuba divers over time. Thus, the impact of diving on pulmonary function largely depends on factors associated with the individual diving exposure. However, in susceptible subjects clinically relevant worsening of lung function may occur even after single shallow-water scuba dives. The effects of diving on pulmonary function largely depend on factors associated with the individual diving response http://ow.ly/aIFS3095WNn